A novel biclustering algorithm of binary microarray data: BiBinCons and BiBinAlter. Issue 1 (June 2015) - Saber, Haifa; Elloumi, Mourad
Abstract The biclustering of microarray data has been the subject of a large research. No one of the existing biclustering algorithms is perfect. The construction of biologically significant groups of biclusters for large microarray data is still a problem that requires a continuous work. Biological validation of biclusters of microarray data is one of the most important open issues. So far, there are no general guidelines in the literature on how to validate biologically extracted biclusters. In this paper, we develop two biclustering algorithms of binary microarray data, adopting theIterative Row and Column Clustering Combination (IRCCC) approach, calledBiBinCons andBiBinAlter . However, theBiBinAlter algorithm is an improvement ofBiBinCons . On the other hand, BiBinAlter differs fromBiBinCons by the use of theEvalStab andIndHomog evaluation functions in addition to theCroBin one (Bioinformatics 20:1993–2003, 2004).BiBinAlter can extracts biclusters of good quality with betterp-values .